Insights into RNAi-based antiviral immunity in Lepidoptera: acute and persistent infections in Bombyx mori and Trichoplusia ni cell lines - Santos, Dulce (Sci Rep, 2018)
The control of viral infections in insects is a current issue of major concern and RNA interference (RNAi) is considered the main antiviral immune response in this group of animals. Here we demonstrate that overexpression of key RNAi factors can help to protect insect cells against viral infections. In particular, we show that overexpression of Dicer2 and Argonaute2 in lepidopteran cells leads to improved defense against the acute infection of the Cricket Paralysis Virus (CrPV). We also demonstrate an important role of RNAi in the control of persistent viral infections, as the one caused by the Macula-like Latent Virus (MLV). Specifically, a direct interaction between Argonaute2 and virus-specific small RNAs is shown. Yet, while knocking down Dicer2 and Argonaute2 resulted in higher transcript levels of the persistently infecting MLV in the lepidopteran cells under investigation, overexpression of these proteins could not further reduce these levels. Taken together, our data provide deep insight into the RNAi-based interactions between insects and their viruses. In addition, our results suggest the potential use of an RNAi gain-of-function approach as an alternative strategy to obtain reduced viral-induced mortality in Lepidoptera, an insect order that encompasses multiple species of relevant economic value.